The Hardiness Level of The Visually Impaired People - Maullasari, Sri; Eddy Wibowo, Mungin; Awalya, Awalya (Jurnal Bimbingan Konseling, 2022)
Individuals with hardiness characteristics can control themselves, commit, face challenges. However, the visually impaired people seem to not show these characteristics proved by the environmental involvement. It is indicated by their inability to manage hardiness, for resistance is needed to boost their toughness. This study attempted to describe the level of the visually impaired people hardiness in Komunitas Sahabat Mata in Semarang City. Through field survey, the researchers involved 50 people with visual impairment using Hardiness Resilience Gauge (HRG) scale to reveal their hardiness level. Findings stated that the female person with visual impairment gained higher hardiness than the male ones, while in terms of gender and age, there found no significant difference between male and female. This study concludes that there is a not correlation between age and hardiness. Further, the findings of this study serve for guidance and counseling services for people with visual impairment.